Community Activity for Providing Motivation about Goals and Hopes for The Better Future - Syukri, Daimon; Admeiva Fitri, Aulia (Andalasian International Journal of Social and Entrepreneurial Development, 2024)
The "Ideals and Hands of Hope" Workshop program was designed to provide 6th grade students of SDN 02 Sungai Tanang with an understanding of the importance of having goals. This workshop, entitled "The Importance of Ideals and Hands of Hope," aims to remind students of the urgency of having ideals and hopes as a guide in life. Goals not only provide focus, but also give meaning to every step of life. Through interactive activities, students will express their ideals, forming commitment and hope for a better future. The "Ideals and Hands of Hope Workshop" program is intended to provide education on the significance of having ideals in life through interactive and fun activities. The students will be asked to put paint on their palms, then stick them back onto a white cloth or banner by writing their names, goals, and ages. This is considered a commitment and hope for the future. By using this creative approach, it is hoped that students will be able to stimulate positive thinking towards their dreams and life goals.